2020
DOI: 10.3390/insects11100686
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Insecticidal Molecule Extracted from Alpinia galanga with Potential to Control the Pest Insect Spodoptera frugiperda

Abstract: Spodoptera frugiperda, a highly polyphagous insect pest from America, has recently invaded and widely spread throughout Africa and Asia. Effective and environmentally safe tools are needed for successful pest management of this invasive species. Natural molecules extracted from plants offer this possibility. Our study aimed to determine the insecticidal efficacy of a new molecule extracted from Alpinia galanga rhizome, the 1′S-1′-acetoxychavicol acetate (ACA). The toxicity of ACA was assessed by topical applic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Several studies have also reported the insecticidal properties of other natural compounds against different insect species. For example, [1′S]-1′-acetoxychavicol acetate isolated from Alpinia galanga exhibited growth inhibition of Spodoptera frugiperda , while having low toxicity to human HepG2 cells compared to insect cells (Ruttanaphan et al 2020). Quercetin isolated from Euphorbia hirta was found to possess various insecticidal properties against S. litura , but had no significant effect on a nontarget earthworm Eisenia fetida Savigny (Selin-Rani et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have also reported the insecticidal properties of other natural compounds against different insect species. For example, [1′S]-1′-acetoxychavicol acetate isolated from Alpinia galanga exhibited growth inhibition of Spodoptera frugiperda , while having low toxicity to human HepG2 cells compared to insect cells (Ruttanaphan et al 2020). Quercetin isolated from Euphorbia hirta was found to possess various insecticidal properties against S. litura , but had no significant effect on a nontarget earthworm Eisenia fetida Savigny (Selin-Rani et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Sf9 cells were derived from the ovary of the S. frugiperda pupa and have been used as a system for the heterologous expression of proteins for several decades ( Altmann et al., 1999 ; van Oers et al., 2015 ). However, they also have been employed to evaluate the potential of certain molecules to act as insecticides ( Pereira et al., 2021 ; Ruttanaphan et al., 2020 ). Indeed, Sf9 cells have been shown to be a useful model responsive to xenobiotics as well as to investigate potential resistance mechanisms ( Cui et al., 2020 ; Giraudo et al., 2011 , 2015 ; Saleh et al., 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, widespread use of these pesticides can lead to pesticide resistance, environmental degradation, contamination of underground water and soil, harming ecosystems and nontarget species, including humans [4][5][6][7][8]. Therefore, curbing synthetic pesticide use is an urgent matter [9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%